DIGITAL INDIA INITIATIVES AND ONLINE EDUCATION SYSTEM IN INDIA AMIDST COVID 19 PANDEMIC - Anil Kumar Biswas (UIN Sunan Gunung Djati Bandung, 2021)
Educational institutions around the world have been closed since the outbreak of the COVID-19 pandemic. Around 1.6 billion students worldwide were forced to be held in these homes. In India, educational institutions were closed in March 2020. As a result, 25 crore students from 15.5 lakh schools were forced to be confined to their homes. The 2009 'Right to Education' Act ensured everyone's education, but the coronavirus outbreak stopped people's basic rights. In this context, various online platforms such as 3 e-learning platforms, namely the National Education Resource Warehouse, DIKSHA, E-Path Sala Simpang Shagun; Swayam, Swayam Prabha, National Academic Depository, National Digital Library and Virtual Labs under the Digital India initiative help further education. But students from vulnerable communities are excluded from the benefits of online education. Seeing this situation, this article analyzes how the traditional education model has stalled due to the outbreak of the pandemic and the government's initiative to continue education. Using qualitative research methods, this article also analyzes India's virtual education infrastructure before and after the pandemic. Analytical work is based on secondary data. The e-platform currently supports learners, but this is not enough to include all. So, there is a need to strengthen the online platform as a mood alternative.